Aquarela [videorecording (Blu-Ray)] (Sony Pictures Home Entertainment, 2019)
A deeply cinematic journey through the transformative beauty and raw power of water. Filmed at a rare 96 frames-per-second, the film is a visceral wake-up call that humans are no match for the sheer force and capricious will of Earth's most precious element. From the precarious frozen waters of Russia's Lake Baikal to Miami in the throes of Hurricane Irma to Venezuela's mighty Angels Falls, water is the main character, with director Victor Kossakovsky capturing her many personalities.